Influence of Economic Policy Uncertainty on Accruals and Abnormal Returns - Santos, Wesley Cirino dos; Souza, Gustavo Henrique Dias; Coaguila, Robert Aldo Iquiapaza; Takamatsu, Renata Turola (Advances in Scientific and Applied Accounting, 2023)
Purpose: To analyze the relationship between economic policy uncertainty in the Brazilian stock market and the accruals anomaly from 2010 to 2019. Method: Time series procedures were performed using the CAPM model, including the accrual factor, in order to obtain the abnormal return. Following this step, we evaluated how the uncertainty of economic policy affected the abnormal return due to accruals, which was calculated using the panel data approach with cluster-robust standard errors. Results and Discussion: The results suggest that economic policy uncertainty influences the abnormal returns due to accruals, indicating that stocks show higher abnormal returns in periods of greater economic policy uncertainty. When considering the volatility index, the results are reversed. In this case, increases in expected volatility can induce investors to sell stocks, reducing stock prices and, consequently, their returns. Nevertheless, rational investors could reap uncertainty premiums as prices recover. Contributions: Economic policy uncertainty, and uncertainty in general, can be regarded as a relevant topic for academia and policymakers, as well as the analysis of the impacts of stock market returns. Moreover, this study can assist portfolio managers and investors in financial markets to improve the stability of policy implementation, avoid abnormal fluctuations in equity markets and suggest investment strategies with perspectives based on economic policy uncertainty and implied market volatility.